2021
DOI: 10.1177/1461348420986645
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation on Axial Rub Impact Dynamic Characteristics of Flexible Rotor Supported by Hybrid Gas Bearings

Abstract: Gas bearings are widely used in micro- and small turbomachinery. Because of the pursuit of high efficiency, turbomachinery adopts small clearance of rotor and stator. The gas bearing rotor system easily suffers from rub impact due to the inherently low damping and load capacity of gas film. Axial rub impact may lead to catastrophic failure of gas bearing rotor system. Previous work put emphasis on radial rub, and only a few papers researched on the axial rub impact by simulation method. In this paper, dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Yang Shuhua [5] et al considered the stiffness of the rotor system support and studied the vibration characteristics of large centrifugal compressor rotors under flexible support. Hao Long [6] et al found that as the damping of the O-ring support increases, the stability of the first-order bending critical speed shaft system also improves, but at the same time, it forces the shaft system to exhibit low-frequency oscillation phenomenon. Wang Jie [7] et al studied the influence of asymmetric support on the critical speed of a dual rotor system.…”
Section: Introductionmentioning
confidence: 99%
“…Yang Shuhua [5] et al considered the stiffness of the rotor system support and studied the vibration characteristics of large centrifugal compressor rotors under flexible support. Hao Long [6] et al found that as the damping of the O-ring support increases, the stability of the first-order bending critical speed shaft system also improves, but at the same time, it forces the shaft system to exhibit low-frequency oscillation phenomenon. Wang Jie [7] et al studied the influence of asymmetric support on the critical speed of a dual rotor system.…”
Section: Introductionmentioning
confidence: 99%